Teachers' Perceptions of the Implementation of Scaffolding-Metacognitive Strategies in Mathematics Learning - Dassa, Awi; Sutamrin; Ihsan, Hisyam; Nasir, Norma; Nurhajarurahmah, St. Zulaiha (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2024)
Scaffolding-metacognitive is a strategy to help students understand mathematical material, but some teachers do not yet understand the extent to which they can use the metacognitive scaffolding strategy in the learning process. This study aims to determine teachers' perceptions of the implementation of scaffolding-metacognitive strategies in mathematics learning in secondary schools. Scaffolding-metacognitive strategies, combining step-by-step teaching with the development of students' awareness and control of their thinking processes, Scaffolding-metacognitive strategies are an effective approach to improving students' understanding of complex mathematical concepts and critical thinking skills. This study used a qualitative descriptive method and the participants consisted of 15 mathematics teachers from several high schools in Makassar City and Gowa Regency. Data were collected through in-depth interviews and direct observation during the learning process. We used the Miles & Huberman analysis framework to analyze the collected data, namely: (1) data reduction; (2) data interpretation and condensation; (3) verification and drawing conclusions. The results of data analysis showed that 60% of teachers did not understand the scaffolding-metacognitive strategy, teachers mentioned several implementation challenges, such as the difficulty of adapting strategies to students' different abilities and limited time to plan and implement learning. In addition, teachers must estimate students' actual and potential knowledge so that teachers can provide scaffolding according to students' needs. Teachers need further support and training to overcome the challenges they face when implementing scaffolding-metacognitive strategies. This research makes an important contribution to the development of more effective educational policies and teacher training programs to improve the quality of mathematics education in secondary schools.